PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD NEGERI 122379 PEMATANGSIANTAR - Simanjuntak, Melvin; Canni Loren Sianturi; Esra Yola Panjaitan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Mind Mapping learning model on the IPAS learning outcomes of fifth-grade students at SD Negeri 122379 Pematangsiantar. This research is a quantitative study, and its research design uses Pre-Experimental with a one-group pretest-posttest design. The population in this study was 20 fifth-grade students at SD Negeri 122379 Pematangsiantar. The sample was a saturated sample, namely 20 fifth-grade students at SD Negeri 122379 Pematangsiantar, consisting of 13 male students and 7 female students. The research data showed that the average pretest score was 39.2, and the posttest score was 79.65. Data analysis was obtained through a paired sample T-test, where the t-calculated value was 11.671 and the t-table value was 1.717, indicating that t-calculated > t-table. Therefore, Ha is accepted, and Ho is rejected. It can be concluded that the Mind Mapping learning model has an effect on the IPAS learning outcomes of fifth-grade students at SD Negeri 122379 Pematangsiantar.